Quality of Life Among Patients with Type 2 Diabetic Mellitus in Outpatient Department, General Public Hospital, West Java - Puspasari, Susy; Farera, Dilo Rivanca (KnE Life Sciences, 2021)
Diabetic Mellitus causes many complications and profoundly affects patients’ lives, impacting their physical, psychological, and social well being. These complications are debilitating and significantly impair their quality of life. However, little is known about the quality of life of patients with type 2 diabetic mellitus in West Java Province, Indonesia, a gap addressed by this study. A cross-sectional survey was conducted in a sample of 73 adult diabetes patients in the outpatient department of a general public hospital in West Java. The survey questionnaire included demographic data and the World Health Organisation (WHO) quality of life markers. The results indicate that of of 73 patients with type 2 diabetic mellitus agreed to join this study, 76.7% were age over 45 years old and 68% were female. The majority of the patients with type 2 diabetic mellitus reported a poor quality of life in 3 domains, physical domain (64.4%), psychological domain (53.4%), and environmental domain (52.1%). The social domain seems more favourable, with 54.8% of respondents reporting a good quality of life. This study indicates the importance of achieving better disease management to improve patient’ quality of life. Keywords: Type 2 diabetic mellitus, quality of life, WHOQOL-BREF